High-resolution printing of micrometer-scale copper electrode: From ink formulation and process optimization to application - Jongyoun Kim; Byeongjae Kang; Hyuntae Kim; Su Hyun Choi; Jaehyoung Park; Hyeonwoo Jung; Youngjun Hwang; Sin Kwon; Kyoohee Woo; Youngu Lee (Journal of Materials Research and Technology, 2024)
In the rapidly advancing field of electronics, there is a growing demand for devices to be miniaturized with high-resolution patterns and compact, straightforward configurations, all while maintaining cost competitiveness. Precision patterning of conductive nano ink based on inexpensive metals offers an effective solution. This technique has proven compatibility with numerous integrated electronics. However, conventional patterning techniques face difficulties achieving high resolution, uniform thickness, and compatibility with environments prone to oxidation. Here, we optimize the reverse offset printing process and its ink formulation for green manufacturing of high-quality, high-resolution conductive micropatterns. The oleate ligand on the surface of Cu nanoparticles (CuNPs) is replaced by polyvinylpyrrolidone, which is more suitable for the steric stabilization of CuNPs in eco-friendly, polar solvent. Then, in consideration of the reverse offset printing mechanism, solvents and additives are evaluated to prepare a reverse offset printable ink. By examining the change in printability according to the composition and process parameters, we determine the printable composition range and process conditions. High-quality CuNP micropatterns with a fine line width of 10 μm, narrow spacing, sharp edge definition, and high uniformity are achieved. Finally, the reverse offset printed CuNP micropatterns are successfully implemented in thermistor microarrays as a potential application.